Knowledge and Practice Regarding Breast Self-Examination among Reproductive Aged Women Attending at TMSS Medical College, Bogura, Bangladesh - Akter, Shormily; Rahman, DM Arifur; Siddique, Md. Kaoser Bin (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Female breast cancer is the second most common cancer globally, and in Bangladesh, it is the leading cause of cancer-related deaths among women. BSE may increase women’s awareness of their own breast health; however, evidence for its impact on mortality reduction is limited, that every woman should practice for early detection. To assess the knowledge and practice of BSE among reproductive aged women attending in the outpatient department of a tertiary care hospital in Bogura, Bangladesh. Materials and Methods: A descriptive cross-sectional study was conducted among 207 women with the age bracket of 15-49 years of age, attending the outpatient department of TMSS Medical College and RCH, Bogura, Bangladesh. Data was collected by interviewer provided with pre-tested structured questionnaire by face to face interview. The knowledge level was measured by five point Likert scale. Data entry was performed in Excel, and descriptive analyses were conducted using SPSS. Results: Total number of respondents was 207. Among them, the overall knowledge level about BSE where individuals regularly check their own breasts to detect any unusual changes was 71% and 21.8% participants did not perform BSE correctly or regularly in relation to their knowledge of BSE. Regarding practice, 63.8% reported performing BSE at least once a month, whereas 21.7% did not practice BSE correctly or regularly. Conclusion: Result suggested that while a majority of women had an average level of knowledge regarding BSE, gaps remain in correct and regular practice. Therefore, targeted health education initiatives are crucial to improve the scenario.